Relationship between obstructive sleep apnea and difficulty of anesthesia induction in children undergoing tonsillectomy. (March 2019) - Jacob, Sarah B.; Smith, Guerin M.; Rebholz, Whitney N.; Cash, Elizabeth D.; Kalathoor, Sasi R.; Goldman, Julie L.; Chandran, Swapna K.
Abstract: Objective: To determine whether anesthesiologists need to rely on polysomnography (PSG) when predicting need for airway intervention during induction in patients with sleep-disordered breathing (SDB). Methods: Prospective case-control observational study at a tertiary care pediatric hospital. Children between the ages of 2–17 undergoing tonsillectomy were divided into three groups: those presenting with OSA observed by history and/or physical examination alone (SDB; n = 33), those with OSA determined by preoperative PSG (OSA; n = 32), and a control group (n = 35) undergoing tonsillectomy for recurrent tonsillitis. An anesthesiologist ranked each case on the level of intervention required to maintain ventilation. Results: Age, height and BMI were associated with greater induction difficulty (r's > .225, p's < .025). Compared to controls, induction difficulty was significantly greater for the SDB group (mean difference = −0.751, 95% confidence interval [CI] = -1.241, -0.261, p = .003), but not for the OSA group (p = .061). No significant difference in induction difficulty was observed between SDB and OSA groups. In a subgroup analysis of the OSA group, an apnea-hypopnea index (AHI) > 10 correlated with increased level of intervention during induction (r = .228, p = .022). Race was also associated with AHI >10 (odds ratio = 3.859, 95% CI = 1.485, 10.03, p = .006). Conclusion: Children with OSA undergoing tonsillectomy require more airway intervention during induction than children with recurrent tonsillitis. Age and BMI were correlated with greater induction difficulty, suggesting that PSG data should be considered in light of these clinical characteristics to ensure an optimal postoperative course for children undergoing tonsillectomy.